Differences of gender in HIV- Risky Sexual Behavior among Adolescents and Parental Support in Luwuk City (Medico Legal Update, 2020)
The proportion of HIV AIDS prevalence currently continues to increase and disparate between women andmen. Aim: to obtain an overview of HIV-risky sexual behavior among adolescents based on gender andparental support. This study was conducted using a cross-sectional study design on 385 adolescents (P = 50%)aged 15-18 years in high schools throughout Luwuk City selected through accidental sampling techniques.Adolescent sexual behavior and parental support were assessed using the Indonesia Global school-basedstudent health survey (GSHS) Questionnaire. There were 26 adolescents (6.8%) had intercourse, men= 22(85%) and women = 4 (15%). 9 adolescents (2.3%) had sex for the first time at age ? 11 years and 7 (1.9%)did it with four or more partners. 8 male adolescents (5.8%) and 1 female (0.4%) had intercourse with menand women (bisexual) and 48.8% of female adolescents did not know how to refuse an invitation to havesex. Parental support like communication is more frequent in females (39%) than males (33%). Betterunderstand the problems of females (43.1%) than males (41.8%). There are still 10% of parents demeaning/dropping other males and 6% female. Most of the risky sexual behavior is found between male, while thesupport and attention of parents are mostly directed to female. There are needs to develop health educationin elementary school to high school and counseling to parents.